Bestiality: A Cruelty Towards Animal - Mabel Chandra; Nitin Nishad; Mahesh A Tripathi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Bestiality is a kind of sexual deviance in which an individual is involved with an animal for the gratificationof his/her sexual desires.It can be considered as a severe form of cruelty towards animals. Few societies inthe world perceived bestiality as a cure for the sexually transmitted disease. However, such conduct is apunishable offense in the Indian legal system under Section- 377 IPC. For many years, animal cruelty hasbeen a concern of both legal and mental health care professionals. The psychological culture in the 1960sacknowledged childhood animal cruelty as a possible risk factor for violent conduct againsthuman beings.The present study aims to provide and explore the issue of human-animal sexual interactions and theirconsequences in society. For this purpose, doctrinal research design has been applied and relevant researcharticles, news reports,and blogs were collected from free online resources and analyzed. This researchdiscusses the various sexual deviations and the types of animals involved, accompanied by a comprehensiveaccount of the results from the few more recent studies. The studyexplains the possible motives for sex withanimals. Besides, how these motives can influence the psychological forensic assessment of offenders whohave sex with animals.